1999
DOI: 10.1002/(sici)1097-4636(1999)48:6<772::aid-jbm2>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extracts from dentin adhesives contain cytotoxic chemicals

Abstract: It was the aim of our study to investigate the composition and cytotoxicity of aqueous elutes from five dentin adhesives currently used in clinical practice: Solobond Plustrade mark, Solisttrade mark, Scotchbond Multipurposetrade mark, Syntac SCtrade mark, and Prime & Bondtrade mark 2.1. Water extracts were analyzed by gas chromatography/mass spectrometry (GC/MS) and relative quantities of identified compounds were compared by means of an internal caffeine standard [%CF]. The in vitro cytotoxic effects of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 26 publications
2
72
0
3
Order By: Relevance
“…A number of studies have used a combined method of gas chromatography and mass spectrometry to determine the organic substances released from different types of RBDF materials [1][2][3][4][5]. These studies have consistently identified unreacted (co)-monomers, such as triethyleneglycol dimethacrylate and hydroxyethyl methacrylate, as well as the initiating additives camphorquinone (CQ), dimethoxybenzoin, dimethylaminoethyl methacrylate (DMA), and dimethyl-p-toluidine (DMT), as common leachates.…”
Section: Introductionmentioning
confidence: 92%
“…A number of studies have used a combined method of gas chromatography and mass spectrometry to determine the organic substances released from different types of RBDF materials [1][2][3][4][5]. These studies have consistently identified unreacted (co)-monomers, such as triethyleneglycol dimethacrylate and hydroxyethyl methacrylate, as well as the initiating additives camphorquinone (CQ), dimethoxybenzoin, dimethylaminoethyl methacrylate (DMA), and dimethyl-p-toluidine (DMT), as common leachates.…”
Section: Introductionmentioning
confidence: 92%
“…[32] In previous cytotoxicity studies, a variety of extraction media have been used such as culture medium,[333435] distilled water,[3637] saline,[32] and acetone plus ethanol in saline. [38] However, only few studies compare the effect of different extraction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of RBCs and adhesives has been studied and it has been shown that, after curing, residual monomers may elute into the oral environment. 7 Dimethacrylates, especially, have been shown to exert cytotoxic 8,9 and endocrine disruptive effects. 10,11 In a clinical situation, unbound components of adhesives and RBCs may diffuse through dentine into the pulp or elute from the restoration into the oral cavity.…”
Section: Introductionmentioning
confidence: 99%